The effect of ludic strategies in the learning process of english grammar in eight grade students at Daniel Octavio Crespo High School - Fuentes, Jacqueline (UDELAS, 2015)
Therefore, this study is important because is trying to prove that ludic strategies are advantageous to teach english to students specially those who are in the firstlevels of high school because that one are the vase as a trampoline for the english language proficiency of the students when they go through the next school levels.